Female Entrepreneurship – An Appropriate Response to Gender Discrimination - Jacques Ascher (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This study aims to discuss one of the most significant economic and social developments in the world – the rise of the female entrepreneurship phenomenon. Women entrepreneurship needs to be studied as a separate field for two main reasons: (a). Female entrepreneurship is an important source of economic growth in creating new jobs and by being genetically different: women provide different solutions to management and business issues; (b). Female entrepreneurship has been neglected, particularly in business research. Although equal opportunity for men and women in the entrepreneurial field is not a reality in the short range, the progress towards its achievement could be facilitated by better understanding of the impact of female entrepreneurship on society and its contribution to economic growth. This study addresses the growth in female entrepreneurship in the developed and developing countries, explores primary motivational and other factors that influence female entrepreneurship, reviews the main obstacles facing the female entrepreneur, and finally makes recommendations to policy-ma